ANALISIS PENGARUH KREATIVITAS PRODUK, VARIASI PRODUK, DAN MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN PADA ANNA CAKE N COOKIES DI SURABAYA - NAFISA, RIZQIYA; Nasution, Ute Chairuz. M; Mulyati, Awin (Research Journal of Social Science and Economics, 2025)
The growth of the culinary industry in Indonesia is currently growing rapidly, resulting in increasingly fierce competition between entrepreneurs. Culinary is no longer a product to meet human needs alone, but has now become a new lifestyle among the people. Industrial growth as it is today also influences consumer purchasing decisions. So that these factors can contribute to each other to increase marketing to consumers to establish strong bonds with companies. This study aims to determine the influence of Product Creativity, Product Variety, and Social Media on Purchase Decisions at Anna Cake N Cookies in Surabaya. This study uses a type of quantitative research. The sample used was 100 respondents who were consumers of Anna Cake N Cookies in Surabaya. Using a non-probability sampling method with a purposive sampling technique. The data collection technique used is by distributing questionnaires online via the Google form. The results of the t test show that the Product Creativity variable has a partial influence on purchasing decisions with the result t count 2.187 > 1.660 . The product variation variable has a partial influence on purchasing decisions with the result t count 4.040 > 1.660 . Social Media variables have no partial influence on purchasing decisions with the result t count 0.943 > 1.660. Then the results of the F test show that Product Creativity, Product Variety, and Social Media have a significant simultaneous effect on Purchase Decisions at Anna Cake N Cookies in Surabaya. Keywords: Product Creativity, Product Variety, Social Media, Buying decision